Overview of Aggressiveness in Early Adolescents Who Play Online Games - Koanda, Naftalen; Rahayu, Puji; Zainuddin, Nurul Inayah (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The purpose of this study is to present a clear picture of aggressiveness among early adolescent online gamers. The research method used is qualitative research with a descriptive approach. The data for this study came from interviews, observations, and literature review. The findings show that violent online games can increase aggression in early adolescents. Physical aggression, verbal aggression, and behavior that damages other people's property are examples of aggressive behavior.